Rumunia i Bułgaria na drodze do Unii Europejskiej (1990–2007) – perspektywa Niemiec i Francji - Ciesielska-Klikowska, Joanna (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2011)
The membership of Romania and Bulgaria in the European Union became a reality in 2007 and was treated as a culmination of a twenty year process in which both countries had to meet the difficult requirements which the Community set. These requirements were more challenging to realize because of the fact that Bucharest and Sofia were forced to introduce severe economic and social reforms, and political changes that led to the transformation of two post-communist republics into parliamentary democracies with well-functioning, free markets. The collapse of the communist era began a new phase in history, whose motto was to establish a ‘return to Europe’. Romania and Bulgaria identified their allies in the Euro-Atlantic organizations, and in cooperation with them they perceived a chance for economic reconstruction and an increase in importance on the international arena. However, the key role on the path of the two Black Sea states to the European Community was played by the Federal Republic of Germany and France, which for the past forty years have been seen as the driving motor of European cooperation. In partnership with these countries, Bucharest and Sofia were trying to implement a plan for their return to Europe. From 1990 both Romania and Bulgaria cooperated with France and Germany in political and economic matters, trying to arouse the interest of leading politicians from Bonn/Berlin and Paris. Although it was clear that the Franco-German pair was emphasizing the commitment of other post-communist countries, such as Poland, the Czech Republic or Hungary, and their leading role among candidates for membership in the EU, it can be said without doubt, that France and Germany were always involved in the process of Euro¬pean enlargement to include the countries on the Black Sea. The article shows the difficult path of Romania and Bulgaria to the European Union, the role of Paris and Bonn/Berlin in the accession negotiations, the decisions made during the presidencies of France and Germany in the Council of the EU, and also stresses the commitment of Bucharest and Sofia to meet the requirements from Copenhagen and their efforts to become members of the Union in 2007.
Romania and Bulgaria on their path towards the European Union (1990-2007) from the point of view of Germany and France